Role of brain-gut-muscle axis in human health and energy homeostasis - Yin, Yunju; Guo, Qiuping; Zhou, Xihong; Duan, Yehui; Yang, Yuhuan; Gong, Saiming; Han, Mengmeng; Liu, Yating; Yang, Zhikang; Chen, Qinghua; Li, Fengna (Frontiers in Nutrition, 2022)
Abstract: The interrelationship between brain, gut and skeletal muscle plays a key role in energy homeostasis of the body, and is becoming a hot topic of research. Intestinal microbial metabolites, such as short-chain fatty acids, bile acids and tryptophan metabolites, communicate with the central nervous system by binding to their receptors. In fact, there is a cross-talk between the central nervous system and the gut. The central nervous system, under the stimulation of pressure, will also affect the stability of the intestinal system, including the local intestinal transport, secretion and permeability of the intestinal system. After the gastrointestinal tract collects information about food absorption, it sends signals to the central system through vagus nerve and other channels to stimulate the secretion of brain-gut peptide and produce feeding behavior, which is also an important part of maintaining energy homeostasis. Skeletal muscle has receptors for short-chain fatty acids and bile acids. Therefore, intestinal microorganisms can participate in skeletal muscle energy metabolism and muscle fiber conversion through their metabolites. Skeletal muscles can also communicate with the gut system during exercise. Under the stimulation of exercise, myokines secreted by skeletal muscle causes the secretion of intestinal hormones, and these hormones can act on the central system and affect food intake. The idea of the brain-gut-muscle axis is gradually being confirmed, and at present it is important for regulating energy homeostasis, which also seems to be relevant to human health. This article focuses on the interaction of intestinal microbial, central nervous, skeletal muscle energy metabolism, and feeding behavior regulation, which will provide new insight into the diagnostic and treatment strategies for obesity, diabetes, and other metabolic diseases.